ICT facilitation of academic assessment process involving individually varied and complex engineering parameter / Mohamad Irwan Pandapotan Harahap - Pandapotan Harahap, Mohamad Irwan (2021)
The advent of the COVID-19 pandemic has assuredly posed a lot of new realities and disruptive challenges to the daily norms of the citizenry across the country. The imperatives at stake are uncompromisable involving human lives and physical and mental health, and the right to receive treatment from the health care providers (The World Health Organization (WHO), n.d.). Coupled with the only possible responses for the moment to this still largely enigmatic disease involves a wide array of restrictions in movement, job performance and personal endeavours, and unfamiliar standard operating procedures (SOPs) involving among other selfprotection, self-cleansing and self-confinement, social distancing. The lives and livelihood of the populace have been irrevocably and massively transformed for better or worse, willingly, or unwillingly into uncharted territories. As we speak, the virus has mutated into more contiguous and deadly variants making the vaccination program and other containment measures even more indispensable and pressing. Health experts have warned that even with the rush in the vaccination program and the attainment of the herd immunity, the disease will remain endemic, and most of the ad hoc SOPs and treatment measures prescribed to deal with the current crisis or some variations of those will likely be here to stay for unforeseeable future. The future seems bleak and uncertain indeed.